COMPLEX IS EASY. A Complex Evolutionary Social System Approach to Global Governance - Emilia Ferone; Andrea Pitasi (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
The goal of this paper is to provide a research based and policy focused general view of a Complex Evolutionary Social System Approach to Global Governance. From this perspective, to frame complex system evolution and global governance it is pivotal to outline two key epistemological distinctions: the one between complex and complicate, and the one between easy and simple. These distinctions will be explained below. Complex is whatever horizon of alternatives whose possible adjacent points require contingent selection according to self-referential coding and programming, nevertheless expanding the self-reproduction of the horizon itself. Complicate means entropy at its highest speed and power – a zero value, time and energy waste organizational model, with an ineffective design, high cost and low return. Examples will be provided also linking these concepts to those of easiness and simplicity.